Application of indirect observation within mixed methods to contrast the results obtained through direct observation: a discussion with observed Pikler educators - Belza, Haizea; Sagastui, Jone; Herrán, Elena (Frontiers in Psychology, 2024)
Introduction. This work arises from a previous research, "Pikler educators early in the morning", carried out in the Emmi Pikler Nursery School in Budapest through Systematic Observation. In it, Piklerian choreographies were found in observed educators’ behavior during the studied three daily activities: feeding breakfast, dressing to go to the garden and free play accompanying. All of them share certain Piklerian which are synthesized in three central keys: the stability of the educator's behavior, her strategic and intentional positioning, and an active emotional control. Objectives. This study aims to contrast this synthesis of results by means of an in-depth interview with the two observed educators, and to apply the methodological approach of indirect observation within mixed methods for its analysis. The objective is to confirm whether the three central keys are recognized as their own and to look for new theoretical-practical elements within the studied educational approach. Materials and methods. We applied an in-depth interview and analyzed it following the guidelines of indirect observation. The participants were the two educators previously observed, a translator from the Pikler team, and the three observers, authors of this work. An ad hoc observation instrument was elaborated, and the three macro-stages QUAL-QUAL-QUAL proposed within mixed methods were rigorously followed. Results. Lag sequential analysis was used to conduct data analyses. We deepened in prospective lags and obtained the response pattern underlying the interview. Then, we performed a concurrence analysis to investigate the relationship between the central keys obtained in our original research and Piklerian ideas. Conclusions. In-depth interview within mixed methods has been a novel and generous tool leading us to substantial and methodological contributions, despite the simplicity of performed analyses. Interviewed educators’ response pattern is a faithful reflection of the Piklerian modus operandi. The study of concurrences shows that Piklerian education is something natural, integrated in its professionals, with the exception of emotional control, which still requires permanent reflection.